FOXO3a Alleviates the Inflammation and Oxidative Stress via Regulating TGF-β and HO-1 in Ankylosing Spondylitis - Xu, Shanshan; Zhang, Xiaoyi; Ma, Yubo; Chen, Yuting; Xie, Huimin; Yu, Lingxiang; Wang, Jinian; Xu, Sheng–qian; Pan, Faming (Frontiers in Immunology, 2022)
This study aimed to investigate whether Forkhead box O3a (FOXO3a) modulates inflammation and oxidative stress in ankylosing spondylitis (AS). We applied bioinformatics analysis, quantitative real-time polymerase chain reaction, immunoblotting, enzyme linked immunosorbent assay, chromatin immunoprecipitation, and dual-luciferase reporter assay. Gene overexpression and knockdown of FOXO3a were conducted via lentivirus and small interfering RNA, respectively. Downregulated FOXO3a expression was first confirmed in AS patients. Interleukin-8 (IL-8) and IL-17A were highly expressed and negatively related with FOXO3a in AS. Total antioxidant capacity (T-AOC) were markedly decreased and positively associated with FOXO3a in AS. Overexpression of FOXO3a inhibited the secretion of inflammatory cytokines and promoted the production of antioxidant enzymes in Jurkat cells. Transforming growth factor-β (TGF-β) and heme oxygenase 1 (HO-1), which had binding sites to FOXO3a based on bioinformatics analysis, were abnormally expressed and positively related with FOXO3a. Accordingly, FOXO3a obviously elevated the protein and transcription levels of TGF-β and HO-1 in Jurkat cells. The above results were verified by silencing FOXO3a. Moreover, FOXO3a directly interacted with and promoted the transcription of TGF-β and HO-1. In summary, the modulation of cellular inflammation and oxidative stress via FOXO3a-mediated TGF-β and HO-1 activation is partly involved in the pathogenesis of AS.